POPULISM AND LEADERSHIP: IS THERE ANYTHING NEW UNDER THE SUN? - SOARE, Sorina (Studia Universitatis Babes-Bolyai Studia Europaea, 2017)
The literature on populism tends to consider dominant leaders as a characteristic feature of populist parties across time and space. However, we know very little about what the populist leadership is about. In this context, this article aims to contribute to a relatively unexplored arena of populist studies, which is what is special about the populist political leadership in an increasingly personalised politics. In the attempt to bridge the literature on populism and personalization of politics, the article argues that populist leadership mirrors the nucleus of the populist discourse. The centrality of the party leader translates in most cases into the emphasis on the unmediated, hence un-institutionalized, genuine democracy that populist parties tend to preach. Because of the veneration of the people, populist leadership is not primarily about communicational skill and (technical) competence but also – first and foremost – a continuously demonstrated trust. Hence the populist leadership is about the mutual pursuit of the people’s interests. Populist leaders must demonstrate by both word and personal example that they are from the people, like the people.